Pemasangan Penerangan Jalan Menggunakan Tenaga Surya di Kampung Pangbogohan Desa Ranca Iyuh - Desryanto, Nurhedhi; Kartika W, R.B. Budi; Fatkhulloh, Amal; Soebiantoro, Rubby; Samanhudi, Asep (Jurnal Pengabdian Kepada Masyarakat, 2022)
Roads are an important aspect for most residents to support various activities so one must pay attention to one of them from the lighting side. With inadequate street lighting conditions, it will certainly cause obstacles to supporting residents' activities at night. Currently, residents of Pangbogohan Village, Ranca Iyuh Village, Tangerang Regency really need street lighting to support residents' activities. In this case, we would like to apply for assistance with the installation of street lighting on Jalan Sujono, Ranca Iyuh Village, Pangbogohan Village, Tangerang Regency. This is in line with the task of lecturers in carrying out the Tri Dharma of Higher Education, one of which is community service activities. The purpose of the installation of street lights is to provide comfort for local residents when they are active at night and avoid things related to the lack of lighting. and calculate the capacity and number of lamps. The result of these activities is the creation of adequate street lighting so that it is of great benefit to local residents